234k views
2 votes
If g(x) is x-3 then what is g(3x)

2 Answers

1 vote

Answer: 3x-3

Work Shown:

g(x) = x-3

g(3x) = 3x-3

We simply replaced every x with 3x. There isn't much else to show in terms of work. I suppose you could factor out the GCF to say g(3x) = 3(x-1), but that isn't much of a simplification in my opinion.

User Pandurang Waghulde
by
6.2k points
2 votes

Answer:

Explanation:

The meaning of g(x) = x - 3 is that whatever you put in the x on the left, you will put in the x on the right.

g(3x) = 3x - 3 is the correct answer.

User Hele
by
5.0k points